Platelet‐mediated angiogenesis is independent of VEGF and fully inhibited by aspirin. (27th August 2013) - Etulain, J; Fondevila, C; Negrotto, S; Schattner, M
<x xml:space="preserve">Abstract</x> Background and Purpose Platelets are major players in every step of vessel development through the local delivery of angiogenesis‐modulating factors, including the pro‐angiogenic protein VEGF and the anti‐angiogenic endostatin. Although thrombin is a potent agonist and is highly elevated in angiogenesis‐related diseases, studies regarding its action on the release of platelet angiogenic factors are scarce and controversial. Herein, we have investigated the role of thrombin not only in VEGF and endostatin release but also in net platelet angiogenic activity. Experimental Approach Human platelets were stimulated with thrombin in the presence of the various inhibitors of the signalling pathways involved in platelet activation. Supernatants/releasates were used to determine the levels of angiogenic molecules and to induce angiogenic responses. Key Results We found that thrombin induced the secretion of both VEGF and endostatin; however, the overall effect of the releasates was pro‐angiogenic as they promoted tubule‐like formation and increased the proliferation of endothelial cells. Both responses were only slightly suppressed in the presence of a VEGF receptor‐neutralizing antibody. Pharmacological studies revealed that while inhibitors of PKC, p38, ERK1/2, Src kinases or PI3K/Akt exerted only partial inhibitory effects, aspirin fully blocked the pro‐angiogenic activity of the releasate. Conclusions and Implications In contrast to current belief, platelet pro‐angiogenic responses are independent of VEGF and appear to be the result of the combined action of several molecules. Moreover, our data reinforce the notion that aspirin is a good candidate for a therapeutic agent to treat angiogenesis‐related diseases.